PENGARUH PENGGUNAAN MEDIA GAMES BLOOKET TERHADAP HASIL BELAJAR SISWA MATERI SUMBER DAYA ALAM - Sephia Ulul Azmi; Ahmad Mulyadiprana; Pidi Mohamad Setiadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to determine the effect of the Treasure Hunt method using Blooket media on the learning outcomes of fifth-grade students in the IPAS subject, specifically the topic of Natural Resources. The problem addressed was the low student performance due to the lack of interactive teaching methods. This research used a quantitative approach with a quasi-experimental design involving two classes: an experimental class and a control class. The instrument used was a 15-item multiple-choice test given before and after the treatment. The results showed that the experimental class had a higher average post-test score than the control class. The N-Gain analysis indicated that most students in the experimental class were in the high and moderately effective categories, while students in the control class were mostly in the moderate and low categories. The Treasure Hunt method with Blooket successfully created an engaging and active learning environment that enhanced students’ cognitive and emotional involvement.